Pengaruh Bukti Fisik, Reliabilitas, Assurance, Daya Tanggap Dan Empati Terhadap Loyalitas Pelanggan Emeralda Golf - Melani Melani; Sujana Sujana; Gen Gen Gendalasari (Jurnal Ilmiah Pariwisata Kesatuan, 2021)
nies. The many competitors in similar companies make each golf club compete to provide services and facilities that support the satisfaction of the golfer and encourage each golfer to be loyal to the products or services offered from each golf course. The purpose of this study is (1) To find the influence of Physical Evidence of the Customer Loyalty (2) To find out the influence of Reliability of the Customer Loyalty, (3) To find the influence of Assurance of the Customer Loyalty. (4) To find out the magnitude of the effect of Responsiveness of the Customer Loyalty. (5) To find out the influence of Empathy of the Customer Loyalty. (6) To find out the influence of Physical Evidence, Reliability, Assurance, Responsiveness and Empathy together of the Customer Loyalty. Keywords: Tangibles, Reliability, Assurance, Responsiveness, Empathy and Customer Loyalty.